Copernican Revolutions: Mary Jo Salter’s Intertextual Interpretation of Paradise Lost in Falling Bodies - Bertoli, Mariacristina Natalia (Miscelánea: A Journal of English and American Studies, 2009)
Intertextuality has often been viewed as the mere rewriting of the plot of a work of literature, thus downplaying the role of structures in creating nets of meaning which cross the boundaries of a single text. By contrast, the present study deals with the meanings attached to traditional structures such as the beginning in medias res (or tragische Analysis). In particular, this article presents the way the manipulation of this device inherited from ancient epics allowed Milton to reverse its original moral implications in Paradise Lost, thus bringing about what John M. Steadman has defined a “Copernican Revolution” in literature. In addition, this study analyzes the reuse of the Miltonic model in Falling Bodies, a play written by the contemporary American poet Mary Jo Salter. Here tragische Analysis is used for bringing about a new Copernican Revolution in which the focus has been shifted from morals to metaliterature. In effect, this structure enables Salter to investigate the very mechanisms of intertextuality and to show that literary recreation never turns upside down the system it belongs to; rather, it enriches the tradition it has stemmed from in a ceaseless process of rewriting and manipulation.